On edge-disjoint pairs of matchings - Vahan V. Mkrtchyan; Vahe L. Musoyan; Anush V. Tserunyan (Изд-во НАН РА)
For a given graph consider the pairs of edge-disjoint matchings whose union contains as many edges as possible, and consider the relation of the cardinality of a maximum matching to the cardinality of the largest matching among such pairs. We show that 5=4 is a tight upper bound for this relation.
Keywords: Mathematics; Graph theory